Food processing in Ghana: Trends, constraints, and opportunities - Andam, Kwaw S.; Silver, Jed (International Food Policy Research Institute, 2016)
As a rapidly-urbanizing, lower middle-income country, Ghana is experiencing diet changes that are spurring a growing demand for processed foods. Recent surveys show significant presence of processed goods in retail shops, including milled rice, processed fruits and vegetables, and frozen meats, but only about a fifth of these products are processed locally. The main reason processing has failed to take off is not lack of policy: Ghana has always been interested in processing of tomatoes, has established a presidential initiative for processing cassava, and aims to process half of the cocoa produced locally. Rather, the main constraint to a vibrant processing sector is the low production and productivity, high cost, and poor quality of local raw materials. This brief describes these key constraints for growing a thriving domestic food processing sector and high-lights some opportunities for growth.